Evaluation of the representative of using rumen fluid samples from lambs fed pelleted TMR for analysis of prokaryotic communities - Ma, Zhiyuan; Zhou, Juwang; Liu, Ting; Zheng, Chen (Frontiers in Microbiology, 2023)
The pelleted TMR pulverized the grass during processing, which may result in more solid attached microorganisms in the filtered rumen fluid. The objective of this study was evaluating the necessity of distinguishing physical phases of rumen contents for analysis of prokaryotes communities in rumen of lambs fed pelleted TMR, considering the dissimilarity of diversity and community of bacteria and archaea between fluid and mixed rumen contents. The yield of microbial DNA, bacterial diversity, abundances of fibrolytic bacteria of phylum Fibrobacterota and Spirochaetota, as well as genus Ruminococcus, Lachnospiraceae_NK3A20, Fibrobacter, and F082, and abundance of archaeal Methanimicrococcus in rumen fluid were lower than those in mixed rumen contents. In conclusion, it is necessary to consider rumen content physical phases when studying the prokaryotic community in rumen of lambs fed pelleted TMR.